Chironomidae (Insecta: Diptera) in three high Andean tropical streams in Colombia: altitudinal and temporal changes - Rojas Céspedes, Mayra Geraldine; Guevara, Giovany; Reinoso Flórez, Gladys (Revista de Biología Tropical, 2024)
Introduction: The Family Chironomidae is recognized for its great abundance and diversity in freshwater ecosystems around the world. However, taxonomic knowledge of this family is limited, particularly in Colombia. Objectives: To estimate the abundance and diversity at the genus level and its spatiotemporal dynamics in three streams, tributaries of the Combeima River in central Colombia. Methods: This study describes the taxonomic and ecological evaluation of chironomid larvae present in three high Andean streams (Tolima, Colombia), called Las Perlas (PE), La Plata (PL) and Cay (CA). Between 2015-2016, six sampling campaigns were conducted in contrasting climatic periods, at nine sampling points (three per stream: upper, middle, and lower). The collections were made with Surber net on different substrates. Results: 15 594 larvae were recorded, corresponding to three subfamilies and 20 genera. The most abundant subfamily was Orthocladiinae with 13 698 larvae (87.84 %), dominated by Cricotopus spp. (66.19 %), followed by Chironominae with 1 367 individuals (8.77 %) and Polypedilum spp. (5.18 %), and Tanypodinae with 530 organisms (3.40 %) and Pentaneura spp. (2.91 %). The highest abundance was found in PL3 (lower part; 27.84 %), followed by CA2 (middle part; 20.47 %) and PE1 (upper part; 1.93 %). The three streams presented the highest abundance during February 2016 (25.93 %; transition to the rainy season), followed by November 2015 (20.59 %; low rainfall) and October 2015 (3.94 %; high rainfall). Conclusions: The results obtained expands the taxonomic lists of chironomids in high Andean areas (1 419-2 586 m), and the detailed characterization of the 20 genera recorded in the selected streams, which constitute relevant contributions for the recognition of these dipterans and their ecological role in the aquatic systems of the Colombian Andes.